How many Polish lives of saints from Piotr Skarga’s “Żywoty świętych” were translated by Eastern Slavs - Sapozhnikova, Galina Nikolaevna (Slavistica Vilnensis, 2019)
The article summarizes the data in the scientific literature on the number of translations from the Polish book of Piotr Skarga’s “Żywoty świętych”, which were made by East Slavic translators on the territory of the Grand Duchy of Lithuania and the Kingdom of Poland. The list of Cyrillic translations from “Żywoty świętych” in the composition of Lviv manuscripts is presented, expanding the number of translations known from the study of F. Thomson in 2003. The list of the lives of the saints who existed in the largest number of lists is given.